Dimensi Culture dalam Perilaku Kesehatan Orang Tua Terhadap Anak Usia Balita di Desa Selandaka, Kabupaten Banyumas - Agung Kurniawan (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2022)
Child health maintenance efforts are aimed at preparing a healthy, intelligent, and qualified generation and to reduce child mortality. Efforts to maintain the health of children are carried out since the fetus is still in the womb, born, after birth, and until the age of 18 (eighteen) years. Child health efforts, among others, are expected to reduce neonatal mortality (AKN), infant mortality (AKB), and toddler mortality (AKBA). Health behavior becomes important to be done by every parent both with the aim to relieve pain and to treat the pain suffered by their children. Related to health behaviors carried out by parents, the cultural dimension is reflected into family habits, especially those carried out by their parents and then passed down to their children. The purpose of this study is to find out the cultural dimension in influencing parents' health behavior in dealing with their child's pain, especially those who are still toddlers. The dimension of culture in relation to the health behavior of parents towards their toddlers who are sick is more due to habits, there are three habits of parents related to health behavior towards their children, namely by using baby shaman massage, treatment to health facilities, and doing self-medication. This happens because the dimension of culture exerts a different influence on each category of informants. The influence is in the form of habits carried out by their families, but also influenced by other factors such as busyness, experience, and education level.